ANALISIS FAKTOR YANG MEMENGARUHI PENGELOLAAN KEUANGAN DESA DI KABUPATEN MEMPAWAH - Risal; Hidayatullah, Ramdani; Mayasafitri, Rina (Program Studi Akuntansi Universitas Panca Bhakti, 2022)
This research was motivated by indications of misappropriation of village funds managed by the village government, and followed up by BPK which turned out to be findings. There are severalfactors that cause this to happen, namely the lack of community involvement in the planning andmonitoring process of village budgets, less than optimal institutions such as the BPD, limitedcompetence of village heads and village officials, and the high political costs of village heads. Thepopulation in this research were villages in Mempawah Regency with a sampling technique usingpurposive sampling with a total sample of 45 villages. The variables in this research are villagefinancial management as the dependent variable, while the independent variables are humanresources, infrastructure, and external monitoring. The results showed that all independent variableshad a positive effect on village financial management in Mempawah Regency.